Sequence; sequence; logarithm!

Algebra Level 3

Consider the recurrence relation a n + 1 a n = 2 n \dfrac{a_{n+1}}{a_n} = 2^n , where n = 1 , 2 , n=1,2,\ldots and a 1 = 1 a_1=1 .

Find the value of log 2 ( a 100 ) \log_2 (a_{100}) .


The answer is 4950.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

4 solutions

As given, we have a n + 1 = 2 n a n a_{n+1}=2^{n}\cdot a_{n} , so: log 2 ( a 100 ) = log 2 ( 2 99 a 99 ) = log 2 ( 2 99 2 98 a 98 ) = \log_{2}(a_{100})=\log_{2}(2^{99}\cdot a_{99})=\log_{2}(2^{99}\cdot 2^{98}\cdot a_{98})=\cdots = log 2 ( k = 1 99 2 k a 1 ) = log 2 ( 2 k = 1 99 k ) =\log_{2}(\displaystyle \prod_{k=1}^{99} 2^{k} \cdot a_{1})=\log_{2}(2^{\sum_{k=1}^{99} k}) = k = 1 99 k log 2 ( 2 ) = 99 100 2 = ( 90 + 9 ) 50 = 4500 + 450 = 4950 =\displaystyle \sum_{k=1}^{99} k \cdot \log_{2}(2)=\frac{99\cdot 100}{2}=(90+9)\cdot 50=4500+450=4950

Irina Stanciu
Jan 3, 2017

We know that: a n + 1 a n = 2 n \frac{a_{n+1}}{a_{n}}=2^{n} , a n a ( n 1 = 2 n 1 \frac{a_{n}}{a_{(n-1}}=2^{n-1} ,..., a 2 a 1 = 2 1 \frac{a_{2}}{a_{1}}=2^{1} We multiply all above in order to reach: a n + 1 a n \frac {a_{n+1}} {a_{n}} a n a ( n 1 ) * \frac{a_{n}}{a_{(n-1)}} . . . a 2 a 1 = 2 n + ( n 1 ) + . . . + 1 * ... * \frac{a_{2}}{a_{1}} =2^{n+(n-1)+...+1} . a n + 1 a n = 2 n ( n + 1 ) 2 \frac {a_{n+1}} {a_{n}} = 2^{ \frac{n(n+1)}{2}} , since 1 + 2 + . . . + n = n ( n + 1 ) 2 1+2+...+n=\frac {n(n+1)}{2} . Then a n + 1 = 2 n ( n + 1 ) 2 a_{n+1}=2^{\frac{n(n+1)} {2} } . a 1 = 2 ( n + 1 ) n 2 a_{1}=2^{\frac{(n+1)n}{2}} Substituting n + 1 n+1 for n n we get a n = 2 n ( n 1 ) 2 a_{n}=2^{\frac{n(n-1)}{2}} and l o g 2 ( a n ) = ( n 1 ) n 2 log_{2} (a_{n})= \frac {(n-1)n}{2} . We need l o g 2 ( a 100 ) = 100. ( 100 1 ) 2 = 50.99 = 4950 log_{2} (a_{100})= \frac{100.(100-1)}{2}=50.99=4950

Very nice problem! Amazing!

Alexander Russou - 4 years, 5 months ago
Zach Abueg
Jan 5, 2017

a n + 1 = 2 n × a n a_{n+1} = 2^n \times a_n

a 1 = 1 = 2 0 a_1 = 1 = 2^0

a 2 = 2 1 × a 1 = 2 1 × 2 0 = 2 1 = 2 0 + 1 a_2 = 2^1 \times a_1 = 2^1 \times 2^0 = 2^1 = 2^{0 + 1}

a 3 = 2 2 × a 2 = 2 2 × 2 1 = 2 3 = 2 0 + 1 + 2 a_3 = 2^2 \times a_2 = 2^2 \times 2^1 = 2^3 = 2^{0 + 1 + 2}

a 4 = 2 3 × a 3 = 2 3 × 2 3 = 2 6 = 2 0 + 1 + 2 + 3 a_4 = 2^3 \times a_3 = 2^3 \times 2^3 = 2^6 = 2^{0 + 1 + 2 + 3}

a 5 = 2 4 × a 4 = 2 4 × 2 6 = 2 10 = 2 0 + 1 + 2 + 3 + 4 a_5 = 2^4 \times a_4 = 2^4 \times 2^6 = 2^{10} = 2^{0 + 1 + 2 + 3 + 4}

a 6 = 2 5 × a 5 = 2 5 × 2 10 = 2 15 = 2 0 + 1 + 2 + 3 + 4 + 5 a_6 = 2^5 \times a^5 = 2^5 \times 2^{10} = 2^{15} = 2^{0 + 1 + 2 + 3 + 4 + 5}

We can generalize this : :

a n = 2 1 + 2 + 3 + . . . + ( n 1 ) a_n = 2^{1 + 2 + 3 + ... + (n - 1)}

Thus,

a 100 = 2 1 + 2 + 3 + . . . + 99 a_{100} = 2^{1 + 2 + 3 + ... + 99}

Recall that the sum of the first n n numbers k = 0 n k = 1 2 ( n ) ( n + 1 ) . \displaystyle \sum_{k=0}^n {k} = \frac 12 (n)(n + 1).

1 + 2 + 3 + . . . + 99 = 100 × 99 2 = 4950 1 + 2 + 3 + ... + 99 = \frac {100 \times 99}{2} = 4950

a 100 = 2 1 + 2 + 3 + . . . + 99 = 2 4950 a_{100} = 2^{1 + 2 + 3 + ... + 99} = 2^{4950}

log 2 ( a 100 ) = log 2 2 4950 = 4950 \log_2 (a_{100}) = \log_2 {2^{4950}} = 4950

a n + 1 a n = 2 n \frac{a_{n+1}}{a_n} = 2^{n} ; and a 1 = 1 a_1 = 1 .

n = 1 a 2 a 1 = 2 a 2 = 2 1 n =1 \Rightarrow \frac{a_2}{a_1} = 2 \rightarrow a_2 = 2^{1}

n = 2 a 3 a 2 = 2 2 a 3 = 2 3 n = 2 \Rightarrow \frac{a_3}{a_2} = 2^{2} \rightarrow a_3 = 2^{3}

n = 3 a 4 a 3 = 2 3 a 4 = 2 6 n = 3 \Rightarrow \frac{a_4}{a_3}= 2^{3} \rightarrow a_4 = 2^{6}

n = 4 a 5 a 4 = 2 4 a 5 = 2 10 n= 4 \Rightarrow \frac{a_5}{a_4} = 2^{4} \rightarrow a_5 = 2^{10}

We now can see that a n = 2 n ( n 1 ) 2 a_n = 2^{\frac{n(n-1)}{2}} .

a 100 = 2 4950 a_{100} = 2^{4950} .

Hence l o g 2 ( a 100 ) = 4950 log_2 (a_{100}) = 4950

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...